A pH-dependent direct sulfhydrylation pathway is required for the pathogenesis of Mycobacterium tuberculosis - Vaibhav Kumar Nain; Vishawjeet Barik; Manitosh Pandey; Mohit Pareek; Taruna Sharma; Rahul Pal; Shaifali Tyagi; Manish Bajpai; Prabhanjan Dwivedi; Bhishma Narayan Panda; Yashwant Kumar; Shailendra Asthana; et al. (Communications Biology)
Abstract Methionine is essential for the growth and survival of Mycobacterium tuberculosis (M. tuberculosis), however, the canonical transsulfuration pathway involved in the biosynthesis of methionine is dispensable, suggesting redundancy. This study explores the presence of an ortholog of O-succinyl homoserine sulfhydrylase in M. tuberculosis, which catalyses direct sulfhydrylation for methionine biosynthesis. Bioinformatics analysis of putative O-succinyl homoserine sulfhydrylase encoded by metZ in M. tuberculosis showed similarities with its orthologues in other bacterial species. Here, we show that metZ deletion in M. tuberculosis resulted in impaired growth under acidic conditions, which was reversed by methionine supplementation. Molecular dynamics simulation studies revealed improved binding of substrate, O-succinyl homoserine, to the active site of MetZ at low pH mimicking the phagosomal microenvironment. Intriguingly, despite higher ATP levels, metZ deletion reduced the frequency of Bedaquiline-induced persister formation. Finally, we demonstrate that loss of metZ hinders M. tuberculosis growth inside the host.